Growth and Performance of Baby Spinach (Spinacia oleracea L.) Grown under Different Organic Fertilizers - C. Parwada; V. Chigiya; W. Ngezimana; J. Chipomho (International Journal of Agronomy)
Spinacia oleracea L. (baby spinach) is a relatively new leaf vegetable crop in Zimbabwe, so the agronomic performance is unknown. A 3-year field experiment was done at the Seke Teachers College research farm, Zimbabwe. The research evaluated the response of baby spinach to different types of organic manure sources, days after fertilizer application (DAS), and growing season. A 3 × 2 factorial in a completely randomized block design (CRBD) with three replicates was used. Baby spinach cultivar, Dash, was grown on three organic manures (goat applied at 14.894 t ha−1, cattle at 17.789 t ha−1, and poultry at 13.807 t ha−1) in winter 2018, 2019, and 2020. Compound D (7% N, 14% P, and 7% K) at 300 kg ha−1 was included as a control. Crop growth rate, leaf area index, leaf area ratio, net assimilation rate, total dry matter production, and harvest index were measured on 7-day intervals from 14 to 35 days after transplanting. Analysis of variance (ANOVA) to compare the effects of the treatments on the baby spinach growth parameters was done. Significant p<0.05 interactions on the type of organic manure × DAS × growing season were observed on all the measured response variables. There were varied effects of organic manures on growth performance at 14 to 28 DAS where poultry manure had higher growth performance compared to cattle and goat manure. Generally, there was a significant p<0.05 gradual increase in growth from 14 to 35 DAS on the organic manures and a decline from day 28 to 35 DAS under compound D. Low quality (large C/N) cattle and goat manure had lower effects than high quality (small C/N) poultry manure at early growth stages of the baby spinach. Unlike compound D, organic manure continuously supplied adequate nutrients throughout the life cycle (35 DAS) of the baby spinach.